Clinical Outcomes of Drug-related Problems in Saudi Arabia: Patients’ and Healthcare Providers’ Perspective - Alomi, Yousef Ahmed; Al-Shaibani, Awatif Saad; Ghadeer, Alfaisal; Alasmi, Njood Mohmmed (Journal of Pharmacy Practice and Community Medicine)
Purpose: To explore the patients and healthcare providers’ attitudes and perceptions on clinical outcomes drug-related problems in Saudi Arabia. Methods: It is a 4-months cross-sectional survey of drug-related problem information in Saudi Arabia. The study consisted of two-part a demographic data. The second part contained the questions about the frequent occurrence of drug-related problems, the type of medication-induced those problems, and the drug-related problem clinical consequences and outcomes. American Society of HealthSystem Pharmacist definitions of drug-related problems used. The 5-point Likert response scale system used. The survey distributed through social media. The questionnaire made of an electronic format, and it analyzed through survey monkey system. Results: The total responders were two hundred and one; the Saudi nationality was 188 (93.5%), and non-Saudi was 13 (6.5%) patient. The gender distribution was female 180 (89.6%), and the male was 21 (10.4%). The majority of them in age (18-44) 88% and located in Riyadh region 84 (41.8%) and Asir region 59 (29.4%). Of those 44 (22.1 %) were healthcare providers. The responders showed a high percentage of drug-related problem consequences and outcomes; drug-related problem lead to pharmacy visit was 59 (29.5%), additional tests were 47 (24.35%), ambulatory care clinic visit was 76 (38.4%), and an emergency visit was 43 (21.4%). The hospital admission was 46 (23.1%), general surgery 24 (11.9%), critical care admission was 24 (12.1%), and drug-induced death was 48 (24.12%). The most frequent drug-related problems occurred with the patient last year at least once; it was drug noncompliance 142 (71.4%), indications without medication 100 (50%), and adverse medication events 80 (40%). The most type of medicines induced the problems were Antibiotics, the drugs for pain, and dermatology drugs. Conclusion: Clinical outcome of drug-related problems occurred was potential. Clinical pharmacy services with emphasis to a drug-related program of antibiotics, painkiller dermatology medications are necessary. Moreover, to patient counseling program in health institutions and public awareness of medications is required in Saudi Arabia.
Keywords: Clinical outcomes; Drug-related problems; Patients; Healthcare providers; Perspective; Saudi Arabia